Accelerating of intense beams of light ions at the MILAC - Bomko, V.A.; Diky, N.P.; Kobets, A.P.; Mazalov, Yu.P.; Ptukhina, Z.E.; Rudjak, B.I.; Sanin, V.M. (Вопросы атомной науки и техники, 1999)
Multicharged ion linear accelerator (MILAC) can be used for effective radionuclide production at NSC KIPT.